Influential attributes for the selection of luxury camping: A mixed-logit method. (September 2019) - Lee, Won Seok; Lee, Joon-Kyu; Moon, Joonho
Abstract: Recently, interest in luxury or glamorous camping, known as glamping, has been rapidly increasing. The purpose of this study is to examine the preferred attributes of glamping by using the choice experiment (CE) method. Although CE has the advantage of evaluating preferred attributes as a form of the 'marginal willingness to pay', the traditional CE analytic method (e.g., multinomial logit model) has been criticized because of the unrealistic assumption that underlies its theoretical basis. Therefore, a more econometrically advanced method, the mixed-logit model, is used to determine the significant variables that affect glamping choices. Five attributes (price, atmosphere, cleanliness, congestion, and security) are selected and tested through a mixed-logit model to estimate the magnitudes of attribute preferences. Suggestions and implications based on the study results are discussed.